Placental Transfusion for Asphyxiated Infants - Katheria, Anup C.; Rich, Wade D.; Bava, Sunita; Lakshminrusimha, Satyan (Frontiers in Pediatrics, 2019)
The current recommendation for umbilical cord management of non-vigorous infants (limp, pale, and not breathing) who need resuscitation at birth is to immediately clamp the umbilical cord. This recommendation is due in part to insufficient evidence for delayed cord clamping (DCC) or umbilical cord milking (UCM). These methods may provide a neuroprotective mechanism that also facilitates cardiovascular transition for non-vigorous infants at birth.